Do vegetables/fruits act as a vehicle in the spread of COVID-19? - Telang, Kapil; Jain, Rahul; Sodani, Ajoy; Shaw, Prachi; Kosta, Susmit (International Journal Of Community Medicine And Public Health, 2020)
The current study was aimed to find out whether the COVID-19 virus is detectable upon the fruits and vegetables after coming in close contact with a patient suffering from nSARS-CoV-2. We included ten subjects, who tested positive for nSARS-CoV-2 RNA within seven days of the experiment. After explaining the experiment, a tray filled with seasonal vegetables and fruits were placed in front of them. The tray remained within their reach, for next thirty minutes. The subjects were requested to remove their face masks and remain so throughout the task. They were requested to manipulate the food articles the way they liked. Subjects were instructed to cough into their hands and then to manipulate each item at least 5 times, during the experiment. Thereafter, the trays were moved into an open and shaded area with free flow of natural air but no direct sunlight. After 1-hour, swabs were taken from surfaces of items by thoroughly rubbing over each of them. Samples were sent immediately to our RT-PCR lab. The nSARS-CoV-2 RNA was not detected, from the samples collected from the fruit/vegetable, at the end of one hour of the direct exposure to the COVID-19 patients. Our results suggest, even after direct exposure to and significant handling by the COVID-19 patients the nSARS-CoV-2 RNA remains undetected after one hour of storage in open. The fruits and vegetables, in real-life situations, are unlikely to act as a fomite and play any significant role in the spread of this disease.